A detailed analysis of possible efficacy signals of NTHi-Mcat vaccine against severe COPD exacerbations in a previously reported randomised phase 2b trial. Issue 41 (29th September 2022) - Arora, Ashwani K.; Chinsky, Kenneth; Keller, Claus; Mayers, Irvin; Pascual-Guardia, Sergi; Vera, Mercè Pérez; Lambert, Christophe; Lombardi, Stefano; Rondini, Simona; Tian, Sun; Ulloa-Montoya, Fernando; Moraschini, Luca; et al.
Highlights: COPD is characterised by episodes of acute worsening of respiratory symptoms called acute exacerbations (AE). No NTHi-Mcat vaccine efficacy (VE) was shown against moderate/severe AE in patients with a history of moderate/severe AE. We conducted secondary analyses on VE against AE to ascertain clinical phenotypes that may benefit from the vaccine. We showed potential VE against severe AE, particularly in frequent exacerbators on inhaled corticosteroid. Abstract: Background: An investigational vaccine containing non-typeable Haemophilus influenzae (NTHi) and Moraxella catarrhalis (Mcat) surface proteins did not show vaccine efficacy (VE) against combined moderate and severe (moderate/severe) exacerbations in a randomised, observer-blinded, placebo-controlled phase 2b trial of patients with chronic obstructive pulmonary disease (COPD). Nevertheless, observations on rates of severe exacerbations and hospitalisations encouraged further evaluation. Methods: Patients with stable COPD (moderate to very severe airflow limitation, Global Initiative for Chronic Obstructive Lung Disease [GOLD] stage 2–4), 40–80 years and at least one moderate/severe exacerbation in the last year received two doses of NTHi-Mcat vaccine or placebo plus standard care. Secondary analyses were conducted on VE against exacerbations according to severity. Potential predictive factors at baseline for VE against severe exacerbations were explored in post-hoc analyses. Results: Of 606 patients enrolled, 571 were included in the efficacy analysis (279 in NTHi-Mcat vaccine group, 292 in placebo group). VE against severe acute exacerbations of COPD (AECOPD) in various subgroups was 52.11 % (p = 0.015; frequent exacerbators), 65.43 % (p = 0.015; baseline GOLD grade 4), 38.24 % (p = 0.034; previous pneumococcal and/or influenza vaccination). VE was 52.49 % (p = 0.044) for the 6–12 months period after 1 month post-dose 2. Multivariable analysis identified two factors (frequent exacerbator status plus inhaled corticosteroid use at baseline) associated with significant VE against severe AECOPD; in this subpopulation, VE was 74.99 % (p < 0.001). Conclusion: Results suggest potential efficacy with the NTHi-Mcat vaccine against severe exacerbations in certain patients with COPD, in particular those who have frequent exacerbations and use inhaled corticosteroids. This potential signal requires confirmation in an appropriately designed prospective clinical trial. Trial registration: ClinicalTrials.gov, NCT03281876.